Comparison of CerviHPV and Hybrid Capture 2 HPV tests for detection of high‐risk HPV infection in cervical swab specimens. Issue 5 (19th December 2018) - Zhao, Guodong; Tian, Yaping; Du, Yingying; Sun, Jinli; Wang, Zhenzhen; Ma, Yong; Zheng, Minxue
Abstract : Background: Persistent high‐risk human papillomavirus (HR‐HPV) infection is the etiological cause of virtually all cervical cancer cases. HR‐HPV screening achieved with earlier generations of HR‐HPV tests has been instrumental in the prevention and early detection of cervical cancer worldwide. The first FDA‐approved HR‐HPV test, digene Hybrid Capture 2 HPV DNA Test (HC2), has been prominent in these efforts. Newer tests have since been developed to improve upon the capability of HC2 test. Methods: To evaluate the performance of a new multiplex real‐time quantitative PCR assay for HR‐HPV detection, CerviHPV HR‐HPV Test (CerviHPV), 232 cervical swab specimens were collected and analyzed by HC2 and CerviHPV tests for comparison. Results: HC2 test detected 69 (29.7%) positive cases, whereas CerviHPV test reported 43 (18.5%) positive cases. The concordance rate between the two tests was 84.5% with a kappa value of 0.579. Additional analyses identified only HPV66 or low‐risk HPV (LR‐HPV) types in six HC2 positive discordant cases, suggesting these HC2 results to be false positive. Conclusion: CerviHPV test has two advantages over HC2 test: It contains a cellular control to eliminate false negative results due to failed sample collection and processing, and it can simultaneously detect and genotype the two most carcinogenic HPV types, HPV16 and 18. In this comparison study, CerviHPV test also demonstrated higher analytical specificity for HR‐HPV genotypes than HC2 test. Therefore, CerviHPV test has the potential to become a viable option for cervical cancer screening in the clinics.